Evaluasi Jumlah Monosit, Jumlah Limfosit dan Kadar Anti Streptolysin-O pada Pasien Tonsilitis Anak - Hanny Dwi Indah Nurcahyani; Dita Pratiwi Kusuma Wardani; Arif Mulyanto; Kurnia Rhitma Dhanti (Jurnal Biodiversitas dan Bioteknologi, 2025)
Tonsillitis is the inflammation of the tonsils that can occur in children, caused by the bacteria Streptococcus haemolyticus and Streptococcus pyogenes. Poor oral hygiene, physical exhaustion, and certain types of food are other risk factors for chronic tonsillitis. When bacteria enter the tonsil tissue, monocytes differentiate into macrophages that destroy foreign objects. Activated lymphocytes differentiate into plasma cells that produce ASO antibodies. This study aims to determine the relationship between the number of monocytes and lymphocytes and Anti-Streptolysin-O levels in pediatric tonsillitis patients. This study was an observational analytical study with a cross-sectional design conducted in July-August 2025 at Dr. R. Goeteng Taroenadibrata Purbalingga Regional General Hospital by measuring the number of monocytes and lymphocytes using a hematology analyzer and Anti-Streptolysin-O levels using the latex agglutination method. The sample size for this study was 32 pediatric tonsillitis patients using accidental sampling. The relationship between monocyte and lymphocyte counts and ASO levels was analyzed using Spearman's rho correlation test. The results of the Spearman's rho correlation test showed that there was no correlation between the number of monocytes and ASO levels (p=0.637, r=0.087) or between the number of lymphocytes and ASO levels (p=0.412, r=-0.150). There was no correlation between the number of monocytes and lymphocytes and ASO levels in pediatric tonsillitis patients. More research is needed on inflammatory markers such as HsCRP, Procalcitonin (PCT) and Interleukin 6 (IL-6).